Analysis of Students’ Learning Interest in SKI Lessons Through the Use of Animated Video Media in Grade 4 Students of MI Islamiyah Sumberwudi - Dandi, Alvin Ilham; Shoimah, Retno Nuzilatus (AJER: Advanced Journal of Education and Religion, 2025)
In the field of education, the success of a learning process can be influenced by many factors, one of which is students’ learning interest. Strong interest can serve as motivation for students to be more active in the learning process. The Islamic Cultural History (SKI) learning process at MI Islamiyah Sumberwudi appeared monotonous and resulted in low student interest, particularly in the material on Isra’ and Mi’raj of Prophet Muhammad (PBUH). This condition demands innovation in learning, one of which is the use of animated videos as a learning medium. The objectives of this study are: (1) to examine the SKI learning process in grade 4 at MI Islamiyah Sumberwudi using animated video media; and (2) to identify the factors that influence students’ learning interest in SKI when using animated video media. This study employed a qualitative method with grade 4 students of MI Islamiyah Sumberwudi as the subjects. Data collection techniques included interviews, observation, and documentation, while data analysis techniques consisted of data reduction, data presentation, and verification. The findings show that: (1) the SKI learning process in grade 4 using animated video media was carried out in three stages—preparation (developing teaching modules and selecting animated videos), implementation (applying the prepared modules), and evaluation (assessing student responses to learning through animated videos); and (2) several factors influenced students’ learning interest in SKI through animated videos, including an engaging storyline, colorful and appealing visuals, attractive characters, and supporting audio elements.